Penerapan Nilai-Nilai Pancasila di Lingkungan Masyarakat - Setyaningtyas, Pramesti; Najicha, Fatma Ulfatun (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2023)
Pancasila is the basis of the state, the method of life, and the way of life of the Indonesian state. Pancasila contains values called Pancasila values. The values of Pancasila will always develop along with the growth of Indonesian citizens. The values of Pancasila are a foundation, basic guideline, guidelines for Indonesian citizens in living the life of the nation and state. The application of Pancasila values can be applied in everyday life in the community. In accordance with the normative and qualitative approach methods based on the journals listed, the discussion is about the application of the values contained in Pancasila which are the norms of life in the community. Without the values of Pancasila, the life of this state will be prone to division.